HUBUNGAN AKHLAK TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Ismatus Sa’adah Harmaen; Muhammad Sofyan; Nasihudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the relationship between students’ morals and cognitive learning outcomes. This research used a quantitative correlational method with questionnaires and tests. The sample consisted of 29 students. The results showed a significant positive correlation between morals and learning outcomes with r value calculated as 0.518. The value of the correlation coefficient is in the interval of 0.40 – 0.59. It means that the relationship between morals and cognitive learning outcomes is not to week. But it is not yet classfied as strong however, this relationship still shows an influence where morals are one of the factors that contribute to the achievement of students cognitive learning outcomes.